Potentially pathogenic Escherichia coli in healthy, pasture-raised sheep on farms and at the abattoir in Brazil - Maluta, Renato Pariz [UNESP]; Fairbrother, John Morris; Stella, Ariel Eurides; Rigobelo, Everlon Cid [UNESP]; Martinez, Roberto; Avila, Fernando Antonio de [UNESP] (Elsevier B.V., 2014)
Sheep harbor pathogenic Escherichia coli, which may cause severe disease in humans. In this study, the prevalence of Shiga toxin-producing E. coli (STEC) and enteropathogenic E. coli (EPEC) was examined in sheep feces and carcasses on three farms and at an abattoir in Brazil. The isolates were further characterized for the presence of markers recently associated with disease in humans, to investigate their possible origin and role as food-borne pathogens. At the abattoir, 99 carcass samples yielded two STEC and 10 EPEC isolates while 101 fecal samples yielded five EPEC and eight STEC isolates. On the other hand, on the farms, 202 samples yielded 44 STEC and eight EPEC isolates. The 77 isolates were typed by PFGE. Isolates with the same PFGE pattern and also those that were not restricted with XbaI were termed as clones (n = 49). The isolates of any one clone mostly originated from the same sampling site. In addition, seven isolates encoded for novel Stx2 variants and five for Stx2e, the subtype related to porcine edema disease, which was for the first time isolated from sheep feces and carcasses. Also, three stx2-only isolates harbored genes of predicted Stx2 variants that were formed by A and B subunits of different types including Stx2a and Stx2d. The EPEC isolates were heterogeneous, 21 (913%) of them possessing efa1, ehxA, lpfA(O113) or paa genes associated with diarrhea in humans. Thus, using markers recently associated with disease, we have demonstrated that E. coli similar to those pathogenic for humans are present in the sheep intestinal microflora, particularly at the abattoir, underlining the potential for food-borne transmission. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Sheep; Food-borne; STEC; EPEC; PFGE; E. coli